NVP-BEZ235 and NVP-BGT226, dual phosphatidylinositol 3-kinase/mammalian target of rapamycin inhibitors, enhance tumor and endothelial cell radiosensitivity - Fokas, Emmanouil; Yoshimura, Michio; Prevo, Remko; Higgins, Geoff; Hackl, Wolfgang; Maira, Sauveur-Michel; Bernhard, Eric J; McKenna, WGillies; Muschel, Ruth J (Radiation oncology (London, England), 2012)
Background The phosphatidylinositol 3-kinase (PI3K)/Akt pathway is activated in tumor cells and promotes tumor cell survival after radiation-induced DNA damage. Because the pathway may not be completely inhibited after blockade of PI3K itself, due to feedback through mammalian target of rapamycin (mTOR), more effective inhibition might be expected by targeting both PI3K and mTOR inhibition. Materials and methods We investigated the effect of two dual PI3K/mTOR (both mTORC1 and mTORC2) inhibitors, NVP-BEZ235 and NVP-BGT226, on SQ20B laryngeal and FaDu hypopharyngeal cancer cells characterised by EGFR overexpression, on T24 bladder tumor cell lines with H-Ras mutation and on endothelial cells. Analysis of target protein phosphorylation, clonogenic survival, number of residual γH2AX foci, cell cycle and apoptosis after radiation was performed in both tumor and endothelial cells. In vitro angiogenesis assays were conducted as well. Results Both compounds effectively inhibited phosphorylation of Akt, mTOR and S6 target proteins and reduced clonogenic survival in irradiated tumor cells. Persistence of DNA damage, as evidenced by increased number of γH2AX foci, was detected after irradiation in the presence of PI3K/mTOR inhibition, together with enhanced G2 cell cycle delay. Treatment with one of the inhibitors, NVP-BEZ235, also resulted in decreased clonogenicity after irradiation of tumor cells under hypoxic conditions. In addition, NVP-BEZ235 blocked VEGF- and IR-induced Akt phosphorylation and increased radiation killing in human umbilical venous endothelial cells (HUVEC) and human dermal microvascular dermal cells (HDMVC). NVP-BEZ235 inhibited VEGF-induced cell migration and capillary tube formation in vitro and enhanced the antivascular effect of irradiation. Treatment with NVP-BEZ235 moderately increased apoptosis in SQ20B and HUVEC cells but not in FaDu cells, and increased necrosis in both tumor and endothelial all cells tumor. Conclusions The results of this study demonstrate that PI3K/mTOR inhibitors can enhance radiation-induced killing in tumor and endothelial cells and may be of benefit when combined with radiotherapy.